Ahmet B. Ercilasun, Kutadgu Bilig Grameri-Fiil, Basin Yayin Yüksekokul Basimevi. Gazi Universitesi Yayin No. 33, Ankara, pp. XII, 196, 1984. - Eleanor Frankle Hecht (El Colegio de México, A.C., 1989)
-